2010
DOI: 10.1515/hf.2010.103
|View full text |Cite
|
Sign up to set email alerts
|

Pore space analysis of beech wood: The vessel network

Abstract: Water transport in wood is vital for the survival of trees. With synchrotron radiation Xray tomographic microscopy (SRXTM), it becomes possible to characterize and quantify the 3D network formed by vessels that are responsible for longitudinal transport. In the present paper, the spatial size dependence of vessels and the organization inside single growth rings in terms of vessel induced porosity was studied by SRXTM. Network characteristics, such as connectivity, were deduced by digital image analysis from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 18 publications
1
47
0
Order By: Relevance
“…A few examples may illustrate this: XCT was applied to study wood species (Trtik et al 2007; Van den Bulcke et al 2009;Svedström et al 2012), wood coatings (Van den Bessières et al 2013), structural changes during drying and modification (Leppänen et al 2011;Van den Bulcke et al 2011;Taylor et al 2013;Biziks et al 2016), archeological wood (Svedström et al 2011), cork (Oliveira et al 2016), fiberboards (Badel et al 2008, Walter andThoemen 2009), wood plastic composites (Defoirdt et al 2010;Schwarzkopf and Muszynski 2015), plywood (Van den Bulcke et al 2011), wood strand composites (Li et al 2016), and wax-impregnation (Scholz et al 2010a,b), just to mention a few. In general, the emerging synchrotron based TM with its high resolution has a great analytical power for wood research (Trtik et al 2007;Hass et al 2010;Zauner et al 2012;Endo and Sugiyama 2013;Baensch et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A few examples may illustrate this: XCT was applied to study wood species (Trtik et al 2007; Van den Bulcke et al 2009;Svedström et al 2012), wood coatings (Van den Bessières et al 2013), structural changes during drying and modification (Leppänen et al 2011;Van den Bulcke et al 2011;Taylor et al 2013;Biziks et al 2016), archeological wood (Svedström et al 2011), cork (Oliveira et al 2016), fiberboards (Badel et al 2008, Walter andThoemen 2009), wood plastic composites (Defoirdt et al 2010;Schwarzkopf and Muszynski 2015), plywood (Van den Bulcke et al 2011), wood strand composites (Li et al 2016), and wax-impregnation (Scholz et al 2010a,b), just to mention a few. In general, the emerging synchrotron based TM with its high resolution has a great analytical power for wood research (Trtik et al 2007;Hass et al 2010;Zauner et al 2012;Endo and Sugiyama 2013;Baensch et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The associated data processing allows acquisition of spatial information even of subcellular structures with a resolution of 0.35 μ m Stampanoni et al 2006a,b ) and observations of different anatomical elements. Both methods provided useful data from in situ mechanical experiments with wood (Trtik et al 2007 ;Walther and Thoemen 2009 ;Hass et al 2010 ;Mannes et al 2010 ), either by means of manual or automatic testing devices (Badel et al 2008 ;Forsberg et al 2008 ). Suitable testing devices seem to be a bottleneck in this type of experiments.…”
Section: Introductionmentioning
confidence: 99%
“…vessels, which were much deeper than the roughness caused by the planing. Anatomical studies of beech have found average vessel diameters of 55.3 µm (Hass et al 2010) and 56.4 µm (by calculation from data presented) (Sass and Eckstein 1995). The deep valleys shown in Figs.…”
Section: Surface Quality-roughness Parametersmentioning
confidence: 91%